Efficacy and tolerability of lamivudine plus dolutegravir as a switch strategy in a multicentre cohort of patients with suppressed HIV‐1 replication. Issue 7 (24th March 2018) - Borghetti, A; Baldin, G; Lombardi, F; Ciccullo, A; Capetti, A; Rusconi, S; Sterrantino, G; Latini, A; Cossu, MV; Gagliardini, R; De Luca, A; Di Giambenedetto, S
Abstract : Objectives: We evaluated the efficacy and tolerability of lamivudine + dolutegravir in a cohort of HIV‐1 infected, treatment‐experienced patients with undetectable HIV‐RNA. Methods: Time to treatment discontinuation (TD) and virological failure (VF) and their predictors were assessed in a multicenter cohort of HIV‐1 infected patients, starting lamivudine + dolutegravir after reaching viral suppression. Secondary objective was the evaluation of changes in lipid profile, renal and immunological functions at week 48. Results: We enrolled 206 patients (72.8% male, with 51 years median age), who mainly switched their antiretroviral therapy for simplification (32.5%) or drug toxicity (54.5%). The estimated probability of maintaining virological suppression at 48 and 96 weeks was 98.2% and 95.1%, respectively. VF was independently predicted by cumulative time on antiretroviral therapy. The estimated probability of remaining on lamivudine plus dolutegravir was 86.7% and 80.5% at week 48 and 96, respectively. A significant improvement in immunological function (CD4 count and CD4/CD8 ratio) was evidenced at week 48, as well as a decrease in total cholesterol/HDL ratio, triglycerides and estimated glomerular filtration rate. Conclusions: Lamivudine plus dolutegravir was effective in maintaining viral suppression in our cohort and led to an improvement in metabolic and immunologic functions.